Đáp án:
Giải thích các bước giải:
x+2,x-3,x-2 lập thành cấp số nhân nên:
$\begin{array}{l}
{\left( {x - 3} \right)^2} = \left( {x + 2} \right)\left( {x - 2} \right)\\
\Rightarrow {x^2} - 6x + 9 = {x^2} - 4\\
\Rightarrow 6x = 9 + 4\\
\Rightarrow x = \dfrac{{13}}{6}
\end{array}$
Do x-1,x+1,y+1 lập thành cấp số cộng nên:
$\begin{array}{l}
x - 1 + y + 1 = 2\left( {x + 1} \right)\\
\Rightarrow x + y = 2x + 2\\
\Rightarrow y = 2x + 2 - x\\
\Rightarrow y = x + 2\\
\Rightarrow y = \dfrac{{13}}{6} + 2 = \dfrac{{25}}{6}\\
Vậy\,x = \dfrac{{13}}{6};y = \dfrac{{25}}{6}
\end{array}$